A Combination of Surgical Techniques to Repair a Giant Traumatic Macular Hole. (9th December 2018) - Ch'ng, Soon Wai; Elaraoud, Ibrahim; Karl, David; Kalogeropoulos, Dimitrios; Lee, Rynn; Carreras, Elisa
Abstract : A 38-year-old man with a traumatic full-thickness macular hole (FTMH) presented to our eye casualty department with a sudden deterioration of his right eye vision to hand movements over the past one week. The suspected traumatic FTMH was present since he was 13 years old from a direct impact of a golf ball in his right eye and his best-corrected visual acuity (BCVA) has always remained at 1/60 Snellen vision. On examination, he had a very large FTMH measuring 1635µ m with central foveal retinal detachment. Pars plana vitrectomy combined with large inverted internal limiting membrane (ILM) peel flap, 5000 Cs silicone oil tamponade, and autologous platelets implantation was performed. Follow-up visits revealed that the FTMH was closed under silicone oil. The silicone oil was removed six months after the surgery and the FTMH remained close with the retina remaining attached. His BCVA was restored to his previous baseline level of 1/60 Snellen vision. With the advent of multiple techniques to repair FTMH such as the ILM flaps, we have combined this technique with older proven techniques such as silicone oil tamponade and autologous platelets implantation to close the giant traumatic FTMH. This case study demonstrates that combining techniques can help close a FMTH that is otherwise deemed impossible in the past.